Macroeconomics of Western Balkans in the context of the global work and business environment - Marković, Mirjana Radović; Đjukanović, Borislav (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"In recent years, there has been an increase in new forms of employment. Namely, thanks to the use of platforms in business and the emergence of the "gig economy", there are gradual changes in this domain. These include part-time, temporary, informal, and unpaid family work. This type of employment can be defined as any job, but only of short or uncertain duration. The experiences gained by the countries of the European Union, as well as the countries of the Western Balkans from the COVID-19 crisis, during which they used new technologies in work, should in the future make working systems even more adapted to the digital age. At last, whether working from home is the product of one's own choice or is the result of a pandemic or other environmental shock, the change in the way work is done is real and governments must understand the implications and take steps to position their economies accordingly"--